Connection between strength and thermal conductivity of metal matrix composites with uniform distribution of graphite flakes. (June 2019) - Mazloum, Aref; Oddone, Valerio; Reich, Stephanie; Sevostianov, Igor
Abstract: The paper focuses on the connection between thermal conductivity and overall strength of metal matrix composites on example of Al2024 and Mg-0.9Ca alloys reinforced with graphite flakes. We combine theoretical and experimental approaches to analyze the maximal stress concentration in such composites as a function of minimal distance between graphite flakes. The latter is linked to the volume fraction of the inhomogeneities, which governs overall thermal conductivity. Elimination of the volume fraction parameter leads to the explicit cross-property connection. This approach is possible if inhomogeneities in the material have the same shape and are uniformly distributed with no distinguishable clusters. The agreement between the theoretical predictions and experimental observations is very good.